2012
DOI: 10.1088/0004-637x/752/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam-Induced Radio Emission From Ultracool Dwarfs

Abstract: We present the numerical simulations for an electron-beam-driven and loss-cone-driven electron-cyclotron maser (ECM) with different plasma parameters and different magnetic field strengths for a relatively small region and short timescale in an attempt to interpret the recent discovered intense radio emission from ultracool dwarfs. We find that a large amount of electromagnetic (EM) field energy can be effectively released from the beam-driven ECM, which rapidly heats the surrounding plasma. A rapidly develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…For the L3.5 dwarf 2MASS J00361617+1821104, Hallinan et al (2008) showed that the radio emission is originally due to the ECM, but perhaps depolarized during propagation toward the observer. In addition, recent particle-in-cell numerical simulations by Yu et al (2012) have shown that, under certain circumstances, maser emission can be intrinsically weakly polarized. The same mechanism can be applied to generate the bright, 100% polarized burst/flare detected from another ultracool dwarf -DENIS-P J104814.9-395604 (Burgasser & Putman 2005).…”
Section: Radiation Mechanisms and Geometric Effectmentioning
confidence: 99%
“…For the L3.5 dwarf 2MASS J00361617+1821104, Hallinan et al (2008) showed that the radio emission is originally due to the ECM, but perhaps depolarized during propagation toward the observer. In addition, recent particle-in-cell numerical simulations by Yu et al (2012) have shown that, under certain circumstances, maser emission can be intrinsically weakly polarized. The same mechanism can be applied to generate the bright, 100% polarized burst/flare detected from another ultracool dwarf -DENIS-P J104814.9-395604 (Burgasser & Putman 2005).…”
Section: Radiation Mechanisms and Geometric Effectmentioning
confidence: 99%
“…To create the framework to model polarised bursts from UCDs, Yu et al (2012) simulated the micro-physics of the immediate environment around late type dwarfs. Other work, such as Kuznetsov et al (2012) and Hallinan et al (2015), have created models which take physically realistic environmental conditions coupled with different geometries for the magnetic field to simulate individual polarised radio bursts.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the ECMI occurs in regions that span a variety of field strengths, so the observed emission has a moderate bandwidth, ∆ν/ν ∼ 1 (Zarka et al 2001), with a cutoff at high frequencies because the body's magnetic field reaches some peak value at its surface. ECMI emission is beamed and likely refracts through the plasmasphere that evidently envelops the radio-active UCDs, necessitating detailed simulations to predict its observed properties (e.g., Kuznetsov et al 2012;Yu et al 2012).…”
Section: Auroral Radio Emissionmentioning
confidence: 99%